Analysis of the RF and noise performance of junctionless MOSFETs using Monte Carlo simulation. (30th September 2013) - Chen, Yongbo; Xu, Ruimin; Crupi, Giovanni; Schreurs, Dominique; Caddemi, Alina
ABSTRACT The dynamic characteristics and high‐frequency noise performance of junctionless (JL) metal‐oxide‐semiconductor field‐effect transistors (MOSFETs) are investigated using a full‐band Monte Carlo simulator. A detailed comparison with conventional inversion mode (IM) MOSFETs is presented. The results of the radio frequency performance indicate that, compared with the traditional IM MOSFET, the JL transistor exhibits lower drain current (Ids), transconductance (gm), and cut‐off frequency (ft) because of its lower electron velocity in the high doping channel. However, owing to a reduced output conductance (gds) and a larger Cgs/Cgd ratio (Cgs is the gate‐to‐source capacitance; Cgd is the gate‐to‐drain capacitance), the JL MOSFET presents an improvement in the intrinsic voltage gain (Avo) and maximum frequency of oscillation (fmax) in comparison with the IM transistor, which makes it be a viable option for the high‐voltage and power gain analog/radio frequency applications. The results of the noise characteristics show that the JL MOSFET exhibits higher minimum noise figure (NFmin) and equivalent noise resistance (Rn), indicating an inferior noise performance. Copyright © 2013 John Wiley & Sons, Ltd.